2020
DOI: 10.1101/2020.02.21.959791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biased localization of actin binding proteins by actin filament conformation

Abstract: The assembly of actin filaments into distinct cytoskeletal structures plays a critical role in cell movement, shape change, and mechanics, but how different sets of proteins localize to these structures within a shared cytoplasm remains unclear. Here, we show that the actin-binding domains of accessory proteins can be sensitive to filament conformational changes induced by perturbations that include other binding proteins, stabilizing drugs, and physical constraints on the filament. Using a combination of live… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…As the actomyosin ring does not form in the absence of anchoring to a branched actin scaffold, one possibility is that these actin/myosin circles are subunits of the actomyosin ring that are unable to assemble into the higher order structure. In this case, linear actin filaments may bend as a result of their association with actin binding proteins (Fassler et al, 2020; Harris et al, 2020; McCullough et al, 2008; Palani et al, 2021). Alternatively, a previous study demonstrated preferential branched actin nucleation on the convex side of bent actin filaments as a likely response to applied forces (Risca et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As the actomyosin ring does not form in the absence of anchoring to a branched actin scaffold, one possibility is that these actin/myosin circles are subunits of the actomyosin ring that are unable to assemble into the higher order structure. In this case, linear actin filaments may bend as a result of their association with actin binding proteins (Fassler et al, 2020; Harris et al, 2020; McCullough et al, 2008; Palani et al, 2021). Alternatively, a previous study demonstrated preferential branched actin nucleation on the convex side of bent actin filaments as a likely response to applied forces (Risca et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The actin binding domains of accessory actin binding proteins are known to be sensitive to actin filament conformational changes. 37 However, how CH1 domain mutations of LCP1 alter its actin bundling property has not been established. Our structural modeling shows that LCP1-ABD1 I232F remains associated with F-actin for a longer period of times than LCP1-ABD1.…”
Section: Discussionmentioning
confidence: 99%
“…Harris et al recently demonstrated that the changes of the actin filament conformation by DrebrinA 1−300 alter the binding kinetics of utrophin actin-binding domain mutants. 28 In addition to the competitive binding as a simple mechanism for the regulation of actomyosin activity, a modulation of the structure of an actin filament in a cooperative manner may be a common ability for other side-binding proteins of the actin filament. The ability of these allosteric inhibitors should support the actomyosin mechanical forces to drive a wide variety of cellular functions.…”
Section: ■ Discussionmentioning
confidence: 99%